China and India's Development Cooperation in Africa The Rise of Southern Powers - Mthembu, Philani (International Political Economy Series,, 2018)
This book offers an explanation of the determinants of China and India's development cooperation in Africa. After collecting over one thousand development cooperation projects by China and India in Africa between 2000 and the present day with the assistance of AidData, it applies the method of qualitative comparative analysis (QCA). The author posits that neither China nor India were solely motivated by one causal factor, whether strategic interests, economic interests, humanitarian interests, or the size of the diaspora. Indeed China and India are driven by multiple and conjunctural causal factors in providing more development cooperation to some countries than others on the African continent. The findings demonstrate the social complexity of the determinants of development cooperation. Indeed only when some of these respective causal factors are combined is it evident that China and India disbursed high levels of development cooperation to some African countries.